Histological and biochemical characterization of oil palm (Elaeis guineensis jacq.) endosperm during fruit development - Kok, Sau Yee (2011)
Oil palm (Elaeis guineensis) is commercially planted in Malaysia and Indonesia for palm oil production. Palm oil has become the largest source of edible oil in the world. With increasing global demand for vegetable oil coupled with the challenges in production, there is an urgent need to improve palm oil productivity. Therefore, in vitro propagation of oil palm has been in progress to regenerate desirable traits in order to meet the world demand. However, the oil palm tissue culture technique is still inefficient and there is also no universal culture medium for all genotypes. One of the focus areas is the optimization of media formulation for enhanced somatic embryogenesis through the understanding of endosperm development. Thus, the aim of this study was to investigate changes in nutrient composition and morphology of endosperm during fruit development. Histological features of oil palm fruits were examined by histochemistry and light microscopy. Oil palm endosperm formation started at 2 weeks after anthesis (WAA) and it was in liquid form. Enlargement of endosperm occurred as the seed developed further. Cellularization occurred at 8 WAA and cells started grow around periphery of the endocarp. The cells in endosperm continued to grow towards the centre of endosperm. The mature endosperm contained numerous nutrient reserves which was essential for nurturing embryo growth. Biochemical compositions in developing oil palm fruits were analysed by chromatographic and atomic spectroscopic techniques. Glutamic acid was the predominant amino acid followed by aspartic acid and arginine throughout the endosperm developmental stages of both planting materials, tenera and clonal. It was suggested that the glutamic acid, aspartic acids and arginine were the main building block in kernel protein. At early stages of seed development, the high hexose/sucrose ratio in tenera (57.85) and clonal (250.53) was observed which is important to meet the high metabolic demand required for cell division and differentiation. However,the ratio was switched at 10WAA in both tenera and clonal (0.80 and 1.53, respectively) which indicated the onset of endosperm maturation phase. Analysis of fatty acids revealed that lauric acid was the most abundant fatty acid in mature oil palm endosperm of tenera (54%) and clonal (51%). The macro and micro mineral elements are essential for plant growth. High amount of manganese and calcium were found at 5 WAA. Manganese content found in tenera and clonal endosperm was 68 mg/100g dw and 158 mg/100g dw, respectively. While, calcium content found in tenera and clonal endosperm was 797 mg/100g dw and 6350 mg/100g dw, respectively. For both tenera and clonal, potassium (108 and 751 mg/100g dw, respectively) and phosphorus (653 and 695 mg/100g dw respectively) were accumulated in mature endosperm. Analyses of vitamins showed that alpha-tocopherol and niacin were the predominant vitamins found in both oil palm endosperms. On the whole, the anatomical and nutritional study of oil palm endosperm has provided information on cellular changes and nutrient requirements for zygotic embryo development. This knowledge will be useful in optimizing the tissue culture media of oil palm in order to improve the efficiency of somatic embryogenesis.